Correction: Water-floating nanohybrid films of layered titanate–graphene for sanitization of algae without secondary pollution. Issue 32 (17th May 2018) - Kim, In Young; Lee, Jang Mee; Hwang, Eui-Ho; Pei, Yi-Rong; Jin, Woo-Bin; Choy, Jin-Ho; Hwang, Seong-Ju
Abstract : Correction for 'Water-floating nanohybrid films of layered titanate–graphene for sanitization of algae without secondary pollution' by In Young Kim et al., RSC Adv., 2016, 6, 98528–98535.